Cold-Acclimation Limits Low Temperature Induced Photoinhibition by Promoting a Higher Photochemical Quantum Yield and a More Effective Psii Restoration in Darkness in the Antarctic Rather Than the Andean Ecotype of Colobanthus Quitensis Kunt Bartl (Cariophyllaceae) - Zuniga-Navarro, G (BioMed Central Ltd., 2012)
Background: Ecotypes of Colobanthus quitensis Kunt Bartl (Cariophyllaceae) from Andes Mountains and Maritime Antarctic grow under contrasting photoinhibitory conditions, reaching differential cold tolerance upon cold acclimation. Photoinhibition depends on the extent of photodamage and recovery capability. We propose that cold acclimation increases resistance to low-temperature-induced photoinhibition, limiting photodamage and promoting recovery under cold. Therefore, the Antarctic ecotype (cold hardiest) should be less photoinhibited and have better recovery from low-temperature-induced photoinhibition than the Andean ecotype. Both ecotypes were exposed to cold induced photoinhibitory treatment (PhT). Photoinhibition and recovery of photosystem II (PSII) was followed by fluorescence, CO2 exchange, and immunoblotting analyses.Results: The same reduction (25%) in maximum PSII efficiency (Fv/Fm) was observed in both cold-acclimated (CA) and non-acclimated (NA) plants under PhT. A full recovery was observed in CA plants of both ecotypes under dark conditions, but CA Antarctic plants recover faster than the Andean ecotype.Under PhT, CA plants maintain their quantum yield of PSII, while NA plants reduced it strongly (50% and 73% for Andean and Antarctic plants respectively). Cold acclimation induced the maintenance of PsaA and Cyt b6/f and reduced a 41% the excitation pressure in Antarctic plants, exhibiting the lowest level under PhT. xCold acclimation decreased significantly NPQs in both ecotypes, and reduced chlorophylls and D1 degradation in Andean plants under PhT.NA and CA plants were able to fully restore their normal photosynthesis, while CA Antarctic plants reached 50% higher photosynthetic rates after recovery, which was associated to electron fluxes maintenance under photoinhibitory conditions.Conclusions: Cold acclimation has a greater importance on the recovery process than on limiting photodamage. Cold acclimation determined the kinetic and extent of recovery process under darkness in both C. quitensis ecotypes. The greater recovery of PSII at low temperature in the Antarctic ecotype was related with its ability to maintain PsaA, Cyt b6/f and D1 protein after photoinhibitory conditions. This is probably due to either a higher stability of these polypeptides or to the maintenance of their turnover upon cold acclimation. In both cases, it is associated to the maintenance of electron drainage from the intersystem pool, which maintains QA more oxidized and may allow the synthesis of ATP and NADPH necessaries for the regeneration of ribulose 1,5-bisphosphate in the Calvin Cycle. This could be a key factor for C. quitensis success under the harsh conditions and the short growing period in the Maritime Antarctic. © 2012 Bascuñan-Godoy et al.; licensee BioMed Central Ltd.